Bilateral Cooperation Between China and Peru Under the Belt and Road Initiative –From Strategic Layout to Future Prospects - Yang, Guo; Maolin, Hu; Zhipeng, Zhang (Archives of Business Research, 2024)
In recent years, the bilateral relationship between China and Peru has developed rapidly, especially with the advancement of China’s Belt and Road Initiative (BRI), leading to significant progress in cooperation across areas such as economy, trade, and investment. As a major country in Latin America, Peru holds unique advantages in terms of its geopolitical location, resource reserves, and market potential, making it a key partner for China within the region. This paper explores the background of Sino-Peruvian relations, the advancement of the BRI in Latin America, and the strategic importance of Peru's Chancay Port project.